Preventive Effects of Health-Food Drinks on the Obesity and DNA Damage of Mice Fed a High-Fat Diet under a Mild Stress - Higashimoto, Minoru; Toda, Chikako; Tokumoto, Nao; Yamauchi, Arinobu (International Journal of Child Health and Nutrition, 2016)
The body weight gain of mice fed an obesity-inducing diet is suppressed by a mild restraint stress, but at the same time, as previously reported, the stress induces DNA damage in the cells of multiple organs. In the present study, we attempted to prevent not only the obesity but also the DNA damage of mice fed an obesity-inducing diet under a mild restraint with commercially available health-food drinks such as fruit and vegetable juices, soymilks, vinegars and lactic acid bacteria drinks, which are rich in antioxidants. The body weight gain of young female mice fed a high-fat diet containing 20% fat for 4 weeks was considerably inhibited by restraint for 15 min per day in weeks 2 to 4 of 4-week period. The inhibition was further promoted with the concomitant administration of health-food drinks noted above, and was accompanied by a decrease of periovular fat, a major abdominal fat in the female mice. The definite loss of energy intake in the mice given health-food drinks was approximately compensated by the energy of the drink administered. On the other hand, the increase of DNA damage generated by restraint in the cells of five organs – the liver, pancreas, spleen, heart and bone marrow – was markedly suppressed with the administration of these drinks. The results suggest that a combination of mild stress and intake of suitable health-food containing some antioxidants may inhibit lifestyle-related diseases including hyperlipidemia and obesity, which may contribute to the inhibition of metabolic syndrome and childhood obesity.